Pneumoperitoneum in a Micropremie: Not Always NEC - Ahmed Khan; Koert de Waal (Case Reports in Pediatrics)
Pneumoperitoneum in the newborn is an acute surgical emergency requiring immediate surgical intervention to ensure survival. It refers to radiological evidence of rupture of an air-containing viscus with resultant soiling of the peritoneal cavity. A female baby was born preterm at 29 weeks with birth weight of 650 grams. She developed abdominal distension on day 6, and abdominal radiography revealed presence of free air in the peritoneum. She proceeded for a laparotomy, and intraoperative findings revealed blood in the peritoneum with an area of inflammation and a small perforation. About 5 cm of the inflamed bowel was resected, and an end to end anastomosis performed. The histopathology of the specimen was consistent with Meckel's diverticulum. Symptomatic Meckel's diverticulum is usually seen in the first two years of life, and perforation is a rare presentation. Perforated Meckel's diverticulum in a premature newborn is very rare, and a review of literature reveals only one other reported case. Newborn Meckel's perforation cases often mimic necrotizing enterocolitis, although many present without any feature of peritonitis. Establishing a preoperative diagnosis of perforated Meckel's is difficult and may not be essential as the treatment remains the same. However, prompt surgical intervention confers a good prognosis in neonates with isolated perforated Meckel's diverticulum.